2020
DOI: 10.1155/2020/9619461
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Adsorption, and Recognition Properties of a Solid Symmetric Tetramethylcucurbit[6]uril-Based Porous Supramolecular Framework

Abstract: In this work, we reported a porous supramolecular framework (A) constructed of a symmetric tetramethylcucurbit[6]uril (TMeQ[6]) in aqueous HCl solutions; the driving force was the outer surface interaction of cucurbit[n]urils, as well as hydrogen bonding between latticed water molecules and portal carbonyl oxygens of TMeQ[6]. Adsorption experimental results revealed that the porous supramolecular framework can absorb certain fluorophore guests (FGs) to form luminescent assemblies (FG@As) by fluorescence enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Phenylpiperazines exhibit good receptor subtype selectivity and urinary tract tissue selectivity, according to studies. Studies on the structure-activity relationship (SAR) of phenylpiperazines have demonstrated this type of compound's ability to inhibit α1 receptor and 5-HT receptor in recent years [39,40] ; the phenylpiperazine part is α1. In studies where receptors bind to drug basic centers, phenylpiperazine can be connected to carriers like anti-heterocyclic rings to give compounds with distinctive pharmacological properties, which can afford control of neuro-drugs and anti-virus agents [41][42][43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…Phenylpiperazines exhibit good receptor subtype selectivity and urinary tract tissue selectivity, according to studies. Studies on the structure-activity relationship (SAR) of phenylpiperazines have demonstrated this type of compound's ability to inhibit α1 receptor and 5-HT receptor in recent years [39,40] ; the phenylpiperazine part is α1. In studies where receptors bind to drug basic centers, phenylpiperazine can be connected to carriers like anti-heterocyclic rings to give compounds with distinctive pharmacological properties, which can afford control of neuro-drugs and anti-virus agents [41][42][43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its good water solubility, TMeQ[6] is often used to replace the insoluble Q[6] in the study of Q[6]-based host–guest chemistry and coordination chemistry, , which are related to the electrostatic potential nearly neutral cavity and negative portal carbonyl oxygen atoms of Q­[ n ]­s. Since 2014, when we first proposed the outer surface interaction of Q­[ n ]­s (OSIQ), particularly self- and anion-induced OSIQs, which relate to the electrostatic potential positive outer surface of Q­[ n ]­s, our group and others have carried out significant works in constructing Q­[ n ]-based supramolecular frameworks based on OSIQs. Further investigations have revealed that Q­[ n ]-based coordination polymers and frameworks can be used for the recovery a variety of metal ions, , the preparation of various sensors, etc. Among these polymers and frameworks, TMeQ[6] has shown diversity in the construction of TMeQ[6]-based supramolecular frameworks. For example, different TMeQ[6]-based supramolecular frameworks can be formed not only in different acid media but also in the same acid medium with different concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…Since 2014, when we first proposed the outer surface interaction of Q­[ n ]­s (OSIQ), particularly self- and anion-induced OSIQs, which relate to the electrostatic potential positive outer surface of Q­[ n ]­s, our group and others have carried out significant works in constructing Q­[ n ]-based supramolecular frameworks based on OSIQs. Further investigations have revealed that Q­[ n ]-based coordination polymers and frameworks can be used for the recovery a variety of metal ions, , the preparation of various sensors, etc. Among these polymers and frameworks, TMeQ[6] has shown diversity in the construction of TMeQ[6]-based supramolecular frameworks. For example, different TMeQ[6]-based supramolecular frameworks can be formed not only in different acid media but also in the same acid medium with different concentrations . In addition, the acquisition of rare Q[7]-based coordination polymers by the accidental introduction of the [CdCl 4 ] 2– anion and the construction of Q­[ n ]-based coordination polymers and supramolecular frameworks by consciously using polychloride anions of various transition metal ions ([M d‑block Cl y ] n − ) were described. , These works not only prompted us to propose the concept of OSIQs but also enabled us to fully realize its important role, particularly for anion-induced OSIQs, in the construction of Q­[ n ]-based coordination polymers and supramolecular frameworks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is precisely because of these structural characteristics that Q[n]s are seeing increased usage in supramolecular chemistry, with progress reported in Q[n]s host-guest chemistry [9][10][11][12][13][14] and Q[n]s coordination chemistry [15][16][17] . Our laboratory and others have been working on Q[n]-based supramolecular frameworks based on OSIQs since 2014 [18][19][20][21][22][23][24] , when we first proposed the outer surface interactions of Q[n]s (OSIQ) [18] , specifically self and anion-induced OSIQs [19] , which involved the electrostatic potential positive outer surface of Q[n]s. Further research has showed that Q[n]-based coordination polymers and frameworks can be utilized to recover a wide range of metal ions [23,24] , as well as to prepare various sensors [25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%